Swimming Program on Mildly Diabetic Rats in Pregnancy - Macedo, Nathália C. D. (2021)
The present study aims to confirm if the moderate-intensity swimming has successful glycemic control and non-toxic oxidative stress levels and to verify the influence on pancreatic adaptations, embryo implantation, and placental efficiency. Female Wistar rats were randomly distributed to obtain mildly diabetic by streptozotocin induction at birth and the non-diabetic females given vehicle. At adulthood, pregnant rats were put at random into sedentary non-diabetic rats (ND); exercise non-diabetic rats (NDEx); sedentary diabetic rats (D); and exercise diabetic rats (DEx). The rats of the groups submitted to moderate intensity carried loads equivalent to 4% of body weight. On day 17 of gestational day, all rats were submitted to oral glucose tolerance test (OGTT). Next day (GD18), the rats were anesthetized and killed to count implantation sites and to collect placentas, blood, and muscle samples for biochemical biomarkers and pancreas for immunohistochemical analysis. The moderate exercise used was not sufficient to stimulate the aerobic pathway but presented positive results on glucose metabolism, lower embryo postimplantation loss, and pancreatic morphology compared with the sedentary diabetic group. However, the DEx group showed muscular damage, decreased antioxidant defense, and lipid peroxidation. Thus, the moderate-intensity exercise reduces glycemic levels during OGTT and causes no damage to non-diabetic rats related to other analyzed parameters in this study. The exercised diabetic rats present better glycemic metabolism in OGTT, islet pancreatic morphology, and embryofetal development. However, it is necessary an adjustment in this exercise intensity to improve the effectiveness of aerobic training for reduction of maternal muscular and lipid membrane damages.